"Games being played": a US exploration of market strategies used by the beverage industry as experienced by food retailers - Megan R. Winkler; Cerra C. Antonacci; Angela Y. Zhang; Melissa N. Laska (BMC, 2024)
Abstract Background The beverage industry's role in undermining nutrition-related population health is a growing global concern. Industry strategies that affect policy, science, and public opinion are increasingly exposed. However, those used in the retail space-known as market strategies-remain largely unspecified. The purpose of this study was to uncover the market strategies beverage companies use with US retailers to secure their influence and control in the primary setting where the public purchases their products-food retail. Methods We conducted a qualitative study based on multiple data sources: 49 interviews with industry insiders, including chain retail managers, independent store owners, and sales representatives and distributors of major food and beverage companies; 15 business files shared by participants, including written beverage marketing agreements and contracts; and 27 purposively sampled, publicly-available industry documents. All data were thematically analyzed. Results We identified that beverage agreements, which dictate the products, space, marketing, and prices of company products in retail settings, are universal regardless of the retailer's market size. While ubiquitous, the agreement terms, services, and treatment beverage companies provided varied widely-with large US retail chains receiving superior opportunities, such as financial incentives and additional services, and independent and small chain retailers often experiencing disadvantaged, more expensive, non-negotiable terms. Despite this, companies also used several strategies that diminished concerns of differential treatment and thus effectively managed their reputation among independent and small chain retailers. Conclusions Findings suggest a use of the consolidated power among beverage companies with significant implications for the healthfulness of food retail settings. We conclude by highlighting key policy and legal targets that could be leveraged in the US to address power imbalances in the retailer-beverage company relationship and ultimately shift retail towards promoting public health.